Trypanorhyncha cestode larvae of hygienic-sanitary importance parasitizing Lobotes surinamensis (Actinopterygii) obtained from fish markets in the state of Rio de Janeiro, Brazil - Diniz, Jéssica Botti; Fonseca, Michelle Cristie Gonçalves da; Gomes, Delir Corrêa; Torres, Eduardo José Lopes; Knoff, Marcelo (Food Science and Technology, 2025)
Lobotes surinamenis is an important fishery resource associated with artisanal fishing, occurring in tropical and subtropical regions throughout the world. Considering the hygienic-sanitary importance of Trypanorhyncha cestode larvae, 50 specimens of L. surinamensis were acquired from fish markets in the state of Rio de Janeiro, from May 2023 to December 2024. The fish were measured, necropsied, filleted, and their organs analyzed. Twenty-two larvae belonging to the following two species of Trypanorhyncha cestode plerocerci were found parasitizing the abdominal cavity and mesentery, Callitetrarhynchus gracilis and C. speciosus, with a prevalence of 10 and 20%, mean intensity of 2.20 and 1.70, and mean abundance of 0.22 and 0.34, respectively. The taxonomic identification of these parasites was based on morphological and morphometric characters using bright-field and scanning electron microscopes. This is the first report of these cestodes parasitizing specimens of L. surinamensis and is an important indicator for establishing fish hygiene control. In addition to repulsiveness, the presence of these cestode plerocerci is a concern due to the probable risk of allergic reactions, thus intensifying the hygienic-sanitary importance of monitoring these parasites to guarantee safe food for consumers.